SARS-CoV-2 infection, not vaccination, the true association between COVID-19 and myocardial infarction mortality: A nationwide study in Ecuador - Esteban Ortiz-Prado; Vladimir Ullauri Solorzano; Diana Moreira-Vera; Jorge Vasconez-Gonzalez; Juan S. Izquierdo-Condoy (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Misinformation linking COVID-19 vaccines to myocardial infarction (MI) has fueled vaccine hesitancy, particularly in high-mortality settings like Ecuador. This study examines the association between COVID-19 infections, vaccinations, and MI mortality to address these concerns. Objective: To investigate whether COVID-19 vaccinations or infections are associated with increased MI mortality in Ecuador. Methods: This descriptive observational ecological time-series study analyzed 710 days of national health registry data from January 2021 to December 2022. The dataset included daily counts of myocardial infarction (MI) deaths, COVID-19 deaths, and COVID-19 vaccinations. Time-series regression models were used to assess the association between MI mortality (outcome) and both COVID-19 deaths and vaccination rates (predictors), with analyses stratified by sex. Results: We recorded a total of 26,637 myocardial infarction (MI) deaths and 24,066 COVID-19 deaths during the study period. Daily COVID-19 deaths were significantly associated with an increase in MI mortality (β = 0.08667, p < 0.0001, R2 = 0.2048), with a stronger effect observed in women (β = 0.1103, p < 0.0001) compared to men (β = 0.07343, p < 0.0001). Additionally, new COVID-19 cases were positively correlated with daily MI deaths (β = 0.002725, p < 0.0001, R2 = 0.2543). In contrast, COVID-19 vaccination rates were associated with a small but statistically significant protective effect against MI mortality (β = −1.188e–5, p = 0.0218, R2 = 0.0074). Conclusion: COVID-19 infection, rather than vaccination, is strongly associated with increased myocardial infarction (MI) mortality in Ecuador. In contrast, the small but statistically significant protective effect observed for vaccination reinforces its cardiovascular safety and public health value. These findings directly counter prevailing misinformation linking vaccines to MI and provide evidence to support vaccination campaigns, particularly in high-risk and high-mortality settings.